Legal Education For Teenagers Regarding The Impact Of Using The Internet After Covid 19 - Rizki Adi Pinandito (International Journal of Law Society Services, 2022)
AbstractWith the increase in people's productive activities by utilizing the internet network, awareness of the use of the internet also increases. In the end, the use of the internet is increasingly popular in every community activity, not only for consumption needs but also for increasing productive activities. The purpose of holding this community service activity is as an educational effort to the community in the Mangunharjo village area, Tembalang District, Semarang City so that they can find out the positive impact of internet use and the negative impact of internet abuse during the COVID-19 pandemic in Indonesia. This community service uses the Participatory Learning Methods (PLM) methodology. The result of this community service is that the community has understood the use of the internet during the pandemic as a means of supporting productivity such as fulfilling educational needs through online learning systems, utilizing digital marketing as an effort for MSMEs to survive in the midst of the economic crisis due to the pandemic until new opportunities are born. improve the welfare of the community after the covid 19 pandemic. The public has also known and understood the dangers of internet abuse during the pandemic, such as the increasing spread of hoax news to the emergence of cyber crime in the community that all parties should be wary of.Keywords: Internet Use, Internet Abuse, Cyber Law, Covid 19, Legal Awareness.